2020
DOI: 10.1093/pcmedi/pbaa022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spaceflight and the cardiovascular system

Abstract: While early investigations into the physiological effects of spaceflight suggest the body's ability to reversibly adapt, the corresponding effects of long-term spaceflight (>6 months) are much less conclusive. Prolonged exposure to microgravity and radiation yields profound effects on the cardiovascular system, including a massive cephalad fluid translocation and altered arterial pressure, which attenuate blood pressure regulatory mechanisms and increase cardiac output. Also, central venous pressure dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…Light ions primarily inhibit the early motile stages of micro-vessel formation, whereas heavy ions prevent the later stages of development, although they also act synergistically (Wuu et al, 2020). In small blood vessels, the inhibition of angiogenesis causes a gradual loss of vessels because of the lack of replacement of damaged vasculature (rarefaction), which leads to pathologies in the deprived tissues (Vernice et al, 2020). On an organismal level, rarefaction eventually causes pain in the extremities, high blood pressure, a longterm increase in the risk of hypertension, arterial thromboembolism, cardiac ischemia, and cardiac dysfunction (Abdel-Qadir et al, 2017).…”
Section: Cardiovascular Dysregulationmentioning
confidence: 99%
“…Light ions primarily inhibit the early motile stages of micro-vessel formation, whereas heavy ions prevent the later stages of development, although they also act synergistically (Wuu et al, 2020). In small blood vessels, the inhibition of angiogenesis causes a gradual loss of vessels because of the lack of replacement of damaged vasculature (rarefaction), which leads to pathologies in the deprived tissues (Vernice et al, 2020). On an organismal level, rarefaction eventually causes pain in the extremities, high blood pressure, a longterm increase in the risk of hypertension, arterial thromboembolism, cardiac ischemia, and cardiac dysfunction (Abdel-Qadir et al, 2017).…”
Section: Cardiovascular Dysregulationmentioning
confidence: 99%
“…It is also reported that active 20S proteasomes within apoptotic exosome-like vesicles can induce autoantibody production and accelerate organ rejection after transplantation ( Dieudé et al., 2015 ), reduce the amount of oligomerized proteins ( Schmidt et al., 2020 ) and reduce tissue damage after myocardial injury ( Lai et al., 2012 ), and are correlated with cancer and other pathological status such as viral infection and vascular injury ( Dieudé et al., 2015 ; Gunasekaran et al., 2020 ; Tugutova et al., 2019 ). The elevated circulating exosomal 20S proteasome in the flight subject may reflect the increased physiological need to clear these proteins resulting from long-term blood, immune, or other physiological disorders caused by various stress factors during the flight or return to gravity ( Ben-Nissan and Sharon, 2014 ; Vernice et al, 2020 ). Study of plasma exosomes obtained from flight subjects at other time points including pre- and inflight will be necessary to further examine whether plasma exosomal proteasome can serve as biomarkers for pathological processes associated with space flight.…”
Section: Discussionmentioning
confidence: 99%
“…Entering into microgravity causes a cephalad shift of body fluids which leads to increased heart stroke volume, a rise in left ventricular end diastolic dimensions and a fluid shift between the vasculature and interstitium [4][5][6]. The fluid shift invokes compensatory endocrine and renal mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%